Interactive implants: vision and challenges - Klaus-Peter Hoffmann; Heidi Olze; Werner Kneist; Thilo Krüger; Wiebke Droste; Marc Ruta; Rüdiger Rupp (Current Directions in Biomedical Engineering, 2018)
Different complex physiological functions might be restored by means of distributed active implants. Wireless communication between the implants, on the one hand, and an external control unit, on the other hand, is necessary to synchronize electrical stimulation of neural and muscular tissue. Seventeen project partners from industries, universities, healthcare providers and research organizations closely cooperate in the framework of the BMBF Innovation Cluster “Interactive Implants (INTAKT)”. The goal of this cluster is to develop and evaluate networks of distributed implants. Challenges of the project include complex interaction between humans and technology, wireless power supply, long-term stability of implants as well as secure and safe signal transmission [1].